Risk, Trust, and Flawed Assumptions: Vaccine Hesitancy During the COVID-19 Pandemic - Ebrahimi, Omid V.; Johnson, Miriam S.; Ebling, Sara; Amundsen, Ole Myklebust; Halsøy, Øyvind; Hoffart, Asle; Skjerdingstad, Nora; Johnson, Sverre Urnes (Frontiers in Public Health, 2021)
Background: The pace at which the present pandemic and future public health crises involving viral infections are eradicated heavily depends on the availability and routine implementation of vaccines. This process is affected by the phenomenon of vaccine hesitancy, among the greatest threats to global health. Methods: This cross-sectional study seeks to investigate the psychological, contextual, and sociodemographic factors associated with vaccination hesitancy in a large sample of 4571 Norwegian adults, recruited through an online survey between January 23 to February 2, 2021. Subgroup analyses and multiple logistic regression were utilized to identify the covariates of vaccine hesitancy. Results: Several subgroups hesitant toward vaccination were identified, including males, rural residents, and parents with children below 18 years of age. No differences were found between natives and non-natives, across education or age groups. Individuals preferring unmonitored media platforms (e.g., information from peers, social media, online forums, and blogs) more frequently reported vaccination hesitance than those relying on information obtainment from source-verified platforms. Perceived risk of vaccination, belief in the superiority of natural immunity, fear concerning significant others being infected, and trust in health officials’ dissemination of vaccine-related information were identified as key variables related to vaccine hesitancy. Conclusions: Given the heterogeneous range of variables associated with vaccine hesitancy, additional strategies to eradicate vaccination fears are called for aside from campaigns targeting the spread of false information. Responding to affective reactions in addition to involving other community leaders besides government and health officials present promising approaches that may aid in combating vaccination hesitation.